2016
DOI: 10.7127/rbai.v10n600514
|View full text |Cite
|
Sign up to set email alerts
|

Irrigação Com Água Salobra Na Cultura Do Rabanete Em Solo Com Fertilizantes Orgânicos

Abstract: A salinidade é um dos principais fatores ambientais que limitam o crescimento e a produtividade agrícola. Objetivou-se com este trabalho avaliar o efeito do estresse salino no crescimento e na produtividade da cultura do rabanete em solo com e sem biofertilizantes. O experimento foi realizado na área experimental da UFC, em Fortaleza-CE, no período de setembro a outubro de 2015. O delineamento experimental foi inteiramente casualizado em esquema fatorial (4 x 3), com cinco repetições. Os tratamentos foram cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
4
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 12 publications
4
4
0
5
Order By: Relevance
“…Sousa et al (2017) found a reduction in the number of leaves when performing a study in saline environment with sunflower cultivation. In accordance with this study, Sousa et al (2016a) also found a reduction in the number of leaves in the corn crop under saline irrigation in a soil with crab biofertilizer.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Sousa et al (2017) found a reduction in the number of leaves when performing a study in saline environment with sunflower cultivation. In accordance with this study, Sousa et al (2016a) also found a reduction in the number of leaves in the corn crop under saline irrigation in a soil with crab biofertilizer.…”
Section: Resultssupporting
confidence: 90%
“…These results are in accordance with those obtained by Cavalcante et al 2011, when they found a decrease in stem diameter in in physic nut (Jatropha curcas L.) plants under saline stress. Results also agree with Sousa et al (2016a), when, evaluating the salt stress in corn plants in a soil with and without biofertilizer prepared with crab remains, found a decline in the stem diameter, in function of water salinity, but with lower intensity in the soil with organic input.…”
Section: /8supporting
confidence: 89%
“…The results were subjected to analysis of variance and regression, and the means were compared by Tukey test with p < 0.05, using the program Assistat 7.7 Beta (Silva & Azevedo, 2016). In the regression analysis, the equations which fitted best to the data were selected based on the significance of regression coefficients at 0.01 and 0.05 significance levels by F test, and on the highest coefficient of determination (R 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Dentre essas hortaliças se destaca o rabanete (Raphanus sativus L.), originário da região mediterrânea e pertencente à família as Brassicaceaes, sendo uma das hortaliças de mais antigo cultivo (CAETANO et al, 2015). É anual de porte baixo, sendo considerada uma opção para o produtor rural, por ser uma das culturas de ciclo mais curto dentre as hortaliças (SOUSA et al, 2016).…”
Section: Produção De Hortaliçasunclassified